Development of a multiplex real time PCR to differentiate Sarcocystis spp. affecting cattle - Moré, Gastón Andrés (2013)
Cattle are intermediate hosts of Sarcocystis cruzi, Sarcocystis hirsuta and Sarcocystis hominis which use canids, felids or primates as definitive hosts (DH), respectively, and in addition of Sarcocystis sinensis from which the DH is unknown. The aims of the present study were to develop and optimize a multiplex real time PCR for a sensitive and specific differentiation of Sarcocystis spp. affecting cattle and to estimate the prevalence of Sarcocystis spp. in Argentinean cattle. The 18S rRNA genes from individual sarcocysts were amplified and cloned to serve as controls. For the amplification of bovine Sarcocystis spp. a total of 3 primers were used in combination with specific individual probes. Each assay was evaluated and optimized individually and subsequently combined in a multiplex assay (BovSarcoMultiplex real time PCR). The analytical specificity of the multiplex assay was assessed using 5. ng of DNA of heterologous Sarcocystis spp. and other apicomplexan parasites, and no positive reactions were observed other than for the species the PCR targeted. The analytical sensitivity ranged between 0.0125 and 0.125. fg of plasmid DNA (equivalent to the DNA of 2-20 plasmid DNA copies) or resembling DNA of 0.1-0.3 bradyzoites. A total of 380 DNA loin samples from Argentina were tested and 313, 29, 14 and 2 were positive for S. cruzi, S. sinensis, S. hirsuta and S. hominis, respectively. S. sinensis was the most prevalent species among thick walled Sarcocystis spp. in Argentinean cattle. Mixed infections were detected in 8.9% of all samples. Diagnostic sensitivity and specificity for the BovSarcoMultiplex real time PCR relative to previous microscopic examination for thin and thick-walled cyst were 91.5% and 41.7%, 36.3% and 95.9% respectively. Improved DNA extraction methods may allow to further increase the specific and sensitive detection of Sarcocystis spp. in meat samples.